Bridging Legal Frontiers: Analyzing Interfaith Marriages between Indonesia and Thailand - An In-Depth Study of Marriage Laws - Maylinda, Prisca Dwi; Biantiputri, Resha; Utami, Safira Maharani Putri; Apriliyatiningsih, Wulan; Simanjuntak, Cintya Hertiana; Ramadhani, Dwi Aryanti (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
Interfaith marriages by Indonesian citizens are currently commonplace even though there are legal and religious regulations that prohibit this act. There are many ways that several parties are still trying to implement and legalize interfaith marriages. Like the case of the interfaith marriage of artist Vidi Aldiano's brother, who got married at the Thai immigration office while maintaining their respective religions. Therefore, this research aims to discuss and analyze: (1) Perspectives of Indonesian Marriage Law and Thai Family Law regarding Interfaith Marriages and (2) Comparison of Registration of Interfaith Marriages in Indonesia and Thailand. This research is normative juridical research with a statutory approach, a comparative approach and a conceptual approach. The research results show that in Indonesia, interfaith marriages held abroad are the authority of the judge to decide whether the marriage is in conflict with the law or not. Meanwhile in Thailand, there are no specific regulations regarding Thai citizens who will enter into marriages abroad with people of different religions. Apart from that, it is necessary to update the Indonesian Marriage Law which specifically regulates the provisions for interfaith marriages as well as adding provisions for interfaith marriages held outside Indonesia as well as harmonizing the Administering Law with the Marriage Law in order to produce laws that do not overlap. In this case, the role of the Indonesian Ulema Council together with the Ministry of Religion is needed optimally to resolve the still confusing issue regarding the legality of registering interfaith marriages, both those held abroad and within the country.